ANALISIS PENINGKATAN KUALITAS PELAYANAN DI CAR WASH OJO LALI DENGAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ilham Baehaqi; Sutresna Juhara; Giyanto Giyanto (Universitas Islam Syekh Yusuf Tangerang, 2026)
This research aims to analyze and improve the service quality at Car wash Ojo Lali in Legok, Tangerang Regency, using the Service Quality (SERVQUAL) and Importance Performance Analysis (IPA) methods. The background of this study is the increasing number of customer complaints, indicating a gap between expectations and actual service performance. A quantitative approach was applied by distributing questionnaires to 30 customers, covering five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The SERVQUAL analysis revealed negative gaps in Tangibles (-0.06), Reliability (-0.06), and Responsiveness (-0.12), indicating dissatisfaction, while Assurance (0.22) and Empathy (0.04) showed positive gaps, indicating satisfaction. The IPA mapped service attributes into four quadrants; washing speed, waiting room comfort, and staff responsiveness were identified as top priorities for improvement, while washing results and complaint handling were priorities to maintain. In conclusion, improvements are needed in responsiveness, reliability, and tangibles through facility upgrades, employee training, and faster service processes to achieve customer satisfaction and loyalty.